Multimaterial Pneumatic Soft Actuators and Robots through a Planar Laser Cutting and Stacking Approach. (5th May 2021) - Luo, Yichi; Zou, Jiang; Gu, Guoying
Abstract : Pneumatic soft robotic systems show remarkable potentials in producing versatile locomotion and manipulations, owing to their flexibility in structural design and material selections. However, fabrication of pneumatic soft robotic systems with complex 3D structures and material distribution still remains elusive. Herein, a mode‐free fabrication approach, called planar laser cutting and stacking fabrication (PLCSF), is proposed to create pneumatic soft robotic systems with multi‐material and complex structure, which involves the following steps: 1) slicing the 3D model of desired pneumatic soft robotic systems into 2D layers; 2) fabricating each layer via laser cutting corresponding 2D membrane; 3) stacking all layers together to finish the fabrication. With the PLCSF approach, various prevalent pneumatic soft actuators are fabricated with complex structures (including fiber‐reinforced and pneu‐net) and different actuation modes (such as bending, elongation, twisting, abduction, contraction, and grabbing). The scalability of the PLCSF approach to fabricate multiple degrees‐of‐freedom (DOFs) pneumatic soft actuators with integrated structures, such as twisting‐bending pneumatic soft actuators for delivering and bending‐elongation‐bending pneumatic soft actuators for crawling, is also demonstrated. It is further demonstrated that the PLCSF approach also enables creating a bio‐inspired soft hand with nine DOFs, capable of various dexterous motions and manipulations. Abstract : Herein, a planar laser cutting and stacking based fabrication approach for pneumatic soft robot systems is presented. Pneumatic soft actuators and robots with various structures (fiber‐reinforced and pneu‐net), multiple materials (stretchable and flexible), and different actuation modes (bending, elongation, twisting, abduction, contraction, and grabbing) are designed, fabricated, and tested to verify the effectiveness of this approach.